Penerapan Kurikulum Merdeka Melalui Model Two Stay Two Stray Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam (PAI) - Silvia, Atik; Rahmawati, Rahmawati (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
of an independent learning curriculum through the Two Stay Two Stray model with the concept of two stay two guests. The research methods used in this study are descriptive qualitative research methods and data collection techniques in the form of observation, unstructured interviews and documentation studies. The result of the implementation of the independent learning curriculum through the Two Stay Two Stray model is able to improve student learning outcomes in PAI subjects is that students who initially learn conventionally by only listening to teacher explanations that tend to be boring can finally play an active role during the learning process. Teachers provide opportunities for students to work together in solving given problems and they help each other to obtain more meaningful learning. Students become more active and motivated so that there is a high curiosity about the material assigned by the teacher. This shows that teachers in designing and creating teaching and learning activities have a very significant influence on student learning outcomes